Challenges, difficulties and barriers for engineering higher education - Miguel Valero (OmniaScience, 2022)
Higher education in general, and in engineering higher education in particular, is constantly under pressure to introduce reforms that improve the employability of graduates. Among the most common claims is the development of a more active and competency-based teaching oriented to the development of professional and personal skills. The university institution responds to these claims, sometimes in a timid way, but others by embarking on great transformation projects. A good example of this is the project to build the European Higher Education Area. However, the challenge of developing a more active and competency-based teaching faces numerous difficulties and barriers because many of the necessary changes are in sharp contrast with a status quo that has been consolidated over centuries. Difficulties and barriers include a lack of deep understanding (and even lack of acceptance) of some of the implications of the challenges we are facing, the learning of new techniques and tools that are not easy to use or unsuitable organizational structures. In this paper, we explore the nature of some of the challenges and review the difficulties and barriers most mentioned most often by those who dare to try. Anyone who wants to address the challenges or has a responsibility to facilitate changes should be aware of all these difficulties and barriers.